The effect of hybrid zinc oxide/graphene oxide (ZnO/GO) nano-catalysts on the photocatalytic degradation of simazine. (November 2020) - Flores, K.; Valdes, C.; Ramirez, D.; Eubanks, T.M.; Lopez, J.; Hernandez, C.; Alcoutlabi, M.; Parsons, J.G.
Abstract: The photocatalytic degradation of simazine (SIM) was investigated using zinc oxide/graphene oxide (ZnO/GO) composite materials under visible light irradiation. The reaction kinetics was studied to optimize the reaction parameters for efficient degradation of SIM. Batch studies were performed to investigate the effects of initial reaction pH, the loading of the ZnO onto GO, and mass of catalyst on the removal of SIM from aqueous solution. A pH of 2 was determined to be the optimal reaction pH for the different ZnO-loaded GO catalysts. In addition, a mass of 40 mg of catalyst in the reaction was observed to be the most effective for the catalysts synthesized using 20 and 30 mmol of Zn 2+ ions; whereas a mass of 10 mg was most effective for the ZnO/GO composite material synthesized using 10 mmol Zn 2+ ions. The reaction was observed to follow a second-order kinetics for the degradation process. Furthermore, the synthesized ZnO/GO composite catalysts resulted in higher reaction rates than those observed for pure ZnO. The 30 mmol ZnO/GO composite expressed a rate of SIM degradation ten times greater than the rate observed for pure ZnO, and sixty-two times greater than the rate of photolysis. In addition, the catalyst cycling exhibited a constant photocatalytic activity for the ZnO/GO composite over three reaction cycles without the need of a conditioning cycle. Highlights: ZnO/GO hybrid material was successfully synthesized and characterized using XRD, SEM, and XPS. The ZnO band gap was observed to shift to approximately 400 nm with the GO support. Effective removal of simazine from aqueous solution under visible light was achieved from pH 2 -pH 8. Kinetics were determined to follow second order as shown below: r a t e = k [ S I M ] 2 [ Z n O G O ] 0 = k [ S I M ] 2 . The effect of temperature on the rate of simazine degradation was dependent on the amount of ZnO present on the GO.